PERANAN PEMERINTAH DAERAH KOTA YOGYAKARTA DALAM PENGELOLAAN PASAR TRADISIONAL DALAM RANGKA MEMPERTAHANKAN EKSISTENSI PASAR TRADISIONAL DI KOTA YOGYAKARTA - , HUSSEINI IRNAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the role of Local Government of Yogyakarta City in Traditional Market management that analyzed thoroughly in relation to the existence of the Traditional Market in Yogyakarta. This study is an empirical legal research that analyzed with descriptive qualitative approach. This study use literature and interviews methods to obtain the data. The interview conducted with stakeholders involved in a Traditional Market system consisting of Government Officials which were represented by 5 (five) institution i.e.: the Regional Development Planning Board, Traditional Market Management Office, Department of Industry, Trade, and Agriculture, Department of Building and Regional Asset, and the Department of Tourism and Culture. Interviews were also conducted with the Traditional Market traders as well as visitors at Traditional Market and expert resources. The result of this study shows that the Local Government of Yogyakarta City represented by 5 (five) institutions have roles as follows: the Regional Development Planning Board have roles as the policy planners and regulates the modern market, Traditional Market Management Office have roles in the management of Traditional Market, Department of Industry, Trade, and Agriculture have roles in the trade aspects, Department of Building and Regional Asset have a role in the construction of the buildings and the facilities, and the Department of Tourism and Culture has a residual role in the promotion. Every institution has obstacles in implementing the role in order to maintain the existence of the Traditional Market. However, not all agencies have made efforts to overcome these obstacles. But in general, the Local Government of Yogyakarta City has managed to maintain the existence of the Traditional Market in Yogyakarta City. However, for other traditional markets such as stalls and private grocery stores, the Local Government of Yogyakarta City still not has a significant role to protect its existence yet.